PERANAN KEYWORD (KATA KUNCI) DALAM IKLAN - Duto Hartanto, Deddi (Institute of Research and Community Outreach - Petra Christian University, 1999)
In the early 1996%2C Sanaflu launched the newest commercial ad themed Fireman. Most people will recognize and remember the words